Fathers Taking Leave: Evaluating the Impact of Shared Parental Leave in the UK - Joanna Clifton-Sprigg; Eleonora Fichera; Ezgi Kaya; Melanie K. Jones (Institute of Labor Economics (IZA), 2024)
We study the effect of the introduction in 2015 of UK Shared Parental Leave policy on the up-take and the length of leave taken by fathers. Using the UK Household Longitudinal Study and Regression Discontinuity in Time, we show that the reform has not affected uptake or length of parental leave reinforcing questions as to its effectiveness.
Keywords: D13; J08; J13; J18; 330; parental leave reform; Regression Discontinuity in Time; UK Household Longitudinal Study